THE NATURE AND OBJECTIVE NEED FOR THE FORMATION OF MATERIAL AND TECHNICAL RESOURCES MARKET IN A MARKET ECONOMY - Ibrahimovich, Rakhimov Bahromjon; ugli, Ibrahimov Behzodbek Bahromjon (The journal of contemporary issues in business and government, 2021)
The establishment of market relations in agriculture requires the development of the system of material and technical resources on the basis of market principles. Weak financial situation of agricultural enterprises, weakening of economic relations with the manufacturer of equipment, transport costs, transit, high customs duties, devaluation of money, imbalances between prices for agricultural and industrial products and a number of other factors.